Windows Vista inside out - Bott, Ed (Microsoft Press, 2007)
Explaining how to use the new features of Windows Vista, a comprehensive manual details hundreds of timesaving solutions, troubleshooting tips, and workarounds, covering the new features of Microsoft Windows Media Player and Microsoft Internet Explorer 7.